2012
DOI: 10.3324/haematol.2011.050187
|View full text |Cite
|
Sign up to set email alerts
|

Cancerous inhibitor of protein phosphatase 2A determines bortezomib-induced apoptosis in leukemia cells

Abstract: ©2013 Ferrata Storti Foundation. This is an open-access paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…In addition, the high-expression level of CIP2A can elevate the drug resistance to doxorubicin in breast cancer (Vaarala et al, 2010). More importantly, it has been shown that CIP2A was the major molecular target in bortezomibinduced apoptosis in many carcinomas (Liu et al, 2013;Tseng et al, 2012). Taken together, CIP2A plays significant role in human cancers.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the high-expression level of CIP2A can elevate the drug resistance to doxorubicin in breast cancer (Vaarala et al, 2010). More importantly, it has been shown that CIP2A was the major molecular target in bortezomibinduced apoptosis in many carcinomas (Liu et al, 2013;Tseng et al, 2012). Taken together, CIP2A plays significant role in human cancers.…”
Section: Discussionmentioning
confidence: 98%
“…Third, a PP2A inhibitor, okadaic acid, significantly reduced the TD-19-induced apoptosis, and a PP2A enhancer, forskolin, increased the apoptotic effect of TD-19 in H460 cells. Taken together, these results indicate that the inhibition of CIP2A and downstream activation of PP2A and inhibition of p-AKT mediated the antitumor effects of TD-19 Huang et al, 2012;Lin et al, 2012;Tseng et al, 2012;Liu et al, 2013;Yu et al, 2013a,b).…”
Section: Discussionmentioning
confidence: 68%
“…For assessment of apoptosis (sub-G1) in primary cells, specific cell death was calculated with the formula: (xt-xm/100-xm)/100, where xt was the number of apoptotic cells in response to a given carfilzomib concentration and xm was the apoptotic cells among the untreated cells (Liu et al, 2013). For assessment of apoptosis (sub-G1) in primary cells, specific cell death was calculated with the formula: (xt-xm/100-xm)/100, where xt was the number of apoptotic cells in response to a given carfilzomib concentration and xm was the apoptotic cells among the untreated cells (Liu et al, 2013).…”
Section: Apoptosis Assaymentioning
confidence: 99%
“…Transfection HL-60 cells were transfected with MYC-tagged KIAA1524 as previously described (Liu et al, 2013). KIAA1524 (CIP2A) cDNA was purchased from Origene (Catalogue number RC219918; Rockville, MD, USA) and constructed into the pCMV6 vector.…”
Section: Apoptosis Assaymentioning
confidence: 99%
See 1 more Smart Citation